Ikkunoita arvioinnin tuolle puolen : uusia avauksia suomalaiseen koulutusta koskevaan evaluaatiokeskusteluun - Vuorenmaa, Maritta (2001)
Assessment and evaluation of education have recently become a legislative obligation in Finland. Yet, discussion on their theoretical premises is relatively rare. The purpose of the present study was to outline a theoretical framework which could be utilised in the evaluation of educational reforms, but the research results can be used in evaluating and conceptualising education in general. The methodology used in the present study was the systematic analysis. The primary data were mainly based on the Finnish discussion on viewing assessment as evaluation published in the 1990' s in our educational journals, which was explored in relation to international and multidisciplinary reference literature. The purpose of evaluation is to collect information needed in determining the value and usefulness of an educational reform and to use this information in the decision-making, monitoring, development and guidance of education. This means that evaluation is a procedure involving policy guidelines, administrative guidance, expert decision-making and in-depth research. In educational policy guidelines utilisation of assessment and evaluation requires that the evaluation procedure has the capacity for intervention, allows stage-by-stage progress and negotiation, follows appropriate policy guidelines, and is based on an analysis of acceptable values. In a decentralised and self-directive system evaluation supports the educational infrastructure, clarifies the responsibilities of the parties involved and co-ordinates the differentiation of the system. Along with the process of evaluation becoming professionalised the function of evaluation will be to maintain interaction between all actors and to exchange and share practical experiences and opinions. Profound understanding of the complexity of the evaluation environment, as well as ability to expand the horizons of knowledge about evaluation are also needed. Evaluation as research can be situated somewhere in between the post-modernist and modernist as well as positivist and constructivist approaches, which forms a challenge for meta-evaluation and for professional experts and their training. The research showed that it would also be necessary to test the ideal models and the framework in evaluation practices and to carry out basic comparative study from the theoretical viewpoint of the evaluation on education and its reforms.